Gravity at the International Criminal Court: admissibility and prosecutorial discretion - Urs, Priya (Oxford monographs in international law, 2024)
'Gravity at the International Criminal Court' analyses the International Criminal Court's application of the sufficient gravity criterion over the last two decades and poses a normative argument in favour of making this application more coherent.